Secondary school students' attitudes to practical work in biology, chemistry and physics in England. Issue 1 (2nd January 2020) - Sharpe, R.; Abrahams, I.
ABSTRACT: Background : In England, practical work is a major part of secondary school science and yet little research has examined students' attitudes specifically to practical work. Purpose : To examine students' attitudes to practical work in biology chemistry and physics in secondary schools in England. Sample : The study involved 607 students from Year 7 to Year 10 (aged 11–15) drawn from three state-maintained secondary schools in England. The schools were, broadly speaking, representative of schools in England in terms of academic measures such as GCSE outcomes, value-added performance and socio-economic area. Design and methods : The research considered students' attitudes in terms of an established analytical framework incorporating the affective, behavioural and cognitive (ABC) domains and used a mixed methods approach involving questionnaires, lesson observations, and focus group discussions. Results : Whilst secondary students' attitudes to practical work were, generally speaking, positive they were not constant and homogenous but change over time. The affective value of practical work was found to vary by subject although in all three sciences this value decreased, albeit at different rates, as students approached their General Certificate in Secondary Education examinations (GCSE) taken at age 16. Conclusion : The affective value of practical work needs to be considered on a subject by subject basis, rather than, as is often the case currently in school, in terms of a generic attitude to science practical work. Furthermore, the affective value of practical work can be maximised by using more at the start of secondary education (Key Stage 3 – ages 11–14) with a gradual, subject-specific, reduction as students approach their summative public examinations (age 16) when their preference for non-practical, exam orientated, teaching increases.